Structuring mechanism of tree species diversity pattern in an evergreen broadleaved forest in Con Dao National Park, Vietnam - Hong Hai, Nguyen; Van Cuong, Le; Van Quy, Nguyen (Journal of Forestry Science and Technology, 2023)
The spatial structure of a community and the ecological mechanisms that control it are central themes in community ecology. This study aimed to investigate the ecological mechanisms driving the coexistence of tree species in the evergreen broadleaved forests in Con Dao National Park, Vietnam. We employed two null models: complete spatial randomness and inhomogeneous Poisson process within the framework of the individual species-area relationship model. The analyses focused on the effects of habitat filtering and species interactions. We discovered habitat heterogeneity in a 4-ha study plot that contained 5,653 tree individuals belonging to sixty-four plant families. The results demonstrated the critical role of habitat filtering and species interactions in maintaining species diversity within the plant community. The study also indicated that the local diversity structure of tree species depended on the spatial scale. This study went beyond niche and neutral theories by emphasizing the significance of ecological field theory and the principle of asymmetric competition in explaining the coexistence of tree species in evergreen broadleaved forests. Our findings may provide valuable insights into biodiversity conservation and the management of evergreen broadleaved forests, helping to improve further plant diversity conservation activities in the study area.